A Virtual Museum Based on a Hindu-Buddhist Kingdom Educational Tour Model to Foster Patriotism - Ni Kadek Dwi Sawitri; I Gusti Agung Ayu Wulandari; Luh Putu Sri Lestari (Universitas Pendidikan Ganesha, 2026)
The low level of patriotism among elementary school students in learning Hindu–Buddhist Kingdoms material is caused by teacher-centered learning, limited learning resources, and the minimal use of interactive media capable of providing concrete visualization of the learning material. These conditions result in suboptimal student engagement in the learning process, thereby requiring technology-based learning media innovations that can provide more contextual and engaging learning experiences. This study aims to analyze the design, feasibility, practicality, and effectiveness of a virtual museum based on the field trip learning model in improving elementary school students’ patriotism. This study employed a research and development approach using the Four-D model, which includes the stages of defining, designing, developing, and disseminating. The research subjects consisted of content experts, instructional design experts, learning media experts, teachers, and elementary school students. Data were collected through observations, interviews, and questionnaires using observation sheets, interview guidelines, and assessment questionnaires. The data were analyzed using descriptive quantitative and inferential analysis techniques. The results showed that the field trip-based virtual museum demonstrated a very high level of feasibility and practicality and was effective in improving students’ patriotism during the learning process. The implications of this study indicate that the field trip-based virtual museum can be utilized as an innovative learning medium to strengthen character education and enhance student engagement in history learning at the elementary school level.